Subacute Brucellosis-induced Guillain-Barré Syndrome: a Case Report - Mehrdad MORADI-PORDANJANI; Ameneh MEHRI-GHAHFARROKHI; Sohrab MORADI-PORDANJANI; Fereidoun RAHMANI (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Guillain-Barré syndrome (GBS) is the most frequent cause of acute flaccid paralysis, and in two-thirds of the patients, antecedent infections have been identified. Brucellosis, a zoonotic disease, rarely leads to GBS. Herein, we present two patients with subacute brucellosis-induced GBS that were diagnosed on the basis of their clinical course and electromyography and nerve conduction velocity study results. There was a 1-month and 5-month interval between the onset of brucellosis and GBS in the two patients. The patients recovered after undergoing plasma exchange, intravenous immunoglobulin administration, and antibiotic therapy. Our findings indicate that physicians should consider brucellosis as a potential etiology of GBS and closely monitor the neurological symptoms of patients with brucellosis.